Second tumors in children with hematological malignancies - N. A. Susuleva; T. T. Valiev; N. S. Martynova; S. N. Mikhaylova (Онкогематология, 2021)
Background. Hemoblastoses treatment success in children made it possible to cure the vast majority of patients. The follow-up period exceeds tens of years, during which the problem of second tumors (ST) becomes urgent.  The objective of the study was to characterize ST in patients who underwent a malignant tumor of hematopoietic and lymphoid tissues at the age of 0 to 18 years.Materials and methods. The study included 64 patients with ST development in the period from 1 to 38 years.Results. Most frequently ST developed after treatment of Hodgkin's lymphoma (45.3 %) and acute lymphoblastic leukemia (35.9 %), supported by high cumulative doses of alkylating agents and radiation therapy. Among STs, in 35.9 % of cases, thyroid cancer was diagnosed, in 10.9 % - acute leukemia, in 9.4 % - tumors of the central nervous system.  The results of ST treatment are significantly worse than those of primary tumors. Thus, of 64 patients with ST, 46 (71.9 %) are alive, death from ST progression was noted in 18 (28.1 %) cases.Conclusion. Improvement of modern treatment protocols aimed at reducing the indications for radiation therapy and cumulative doses of alkylating agents, along with the development of effective follow-up programs for children cured of hematological malignancies, will probably help reduce the ST incidence.